Mesospheric Dust - radar applications for detection and investigation - Gunnarsdottir, Tinna Lif (UiT Norges arktiske universitet, 2023)
Large amounts of meteoric particles ablate globally into the Earth’s atmosphere each day, and they interact with the atmosphere through several processes in the mesosphere and below. These processes include dust charging, where dust is expected to influence the charge balance in the D-region of the ionosphere. Consequently, the charged dust particles can influence the incoherent scatter that is observed from the ionospheric plasma with radar. Dust also plays a role in the formation of ice particles, and charge interactions of these ice particles take part in a process that forms coherent radar echoes called Polar Mesospheric Summer Echoes (PMSEs). Therefore, radar investigations offer the possibility to investigate the dust and its interactions. Based on observations with the EISCAT VHF radar, this thesis deals with different radar methods and their possibilities to examine dust particles throughout the year, both looking at dust signatures in incoherent scatter signals as well as dust encased in ice in the cold summer mesosphere and its influence on PMSEs. Examining dust signatures in incoherent scatter we have found that it is possible to derive dust size and number density information, as long as the electron density is sufficiently high to provide signals that allow for detailed analysis of the spectral shapes. However, this is often not the case, making long-term investigations of the D-region quite difficult. The emergence of the new EISCAT_ 3D radar with a higher transmit power compared to the present EISCAT radar used for our studies can improve observational studies, providing information on the intricacies of dust clouds. An existing model to describe the incoherent scatter in the presence of charged dust was extended, and a code was made public for future use to calculate the spectra including dust with a size distribution. We studied PMSEs in combination with artificial heating of the ionospheric electrons at cyclic time intervals. We investigated observations during low solar illumination conditions ...